Application of cupping therapy with buffalo horns for patients with cervical spondylosis (牛角罐法在颈型颈椎病患者中的应用) - HE Shuiwen (何水文); JIANG Haijun (蒋海军); YU Yuxiu (于玉秀); OU Jinshi (欧金石) (Association of Integrative Nursing, 2023)
Objective To investigate the clinical effect of cupping therapywith buffalo horn in the treatment of cervical spondylosis. Methods Totally60 patients with cervical spondylosis were randomly divided into control group and observation group, with 30 cases in each group. All patients received conventional treatment, and those in the observation group received cupping therapy by using buffalo-horn cupping device. The scores of Visual Analogue Scale on pain (VAS) and Neck Disability Index (NDI) before and after treatment were compared between the twogroups, and the therapeutic effect was evaluated. Results The scores of VAS and NDI were reduced in both two groups after intervention, and scores of VAS and NDI in the observation group were lower than those in the control group, with a significant difference (P＜0. 01). The overall effective rate of intervention in the observation group was higher than that in the control group (P＜0. 05). Conclusion The cupping therapy with buffalo horn can improve the neck function and relieve the pain of patients with cervical spondylosis. (目的 观察牛角罐法治疗颈型颈椎病的临床疗效。方法 将60例颈型颈椎病患者按随机数字表法随机分为对照组和观察组, 各30例。对照组采用常规治疗, 观察组在常规治疗的基础上增加牛角罐法。对比两组患者治疗前后疼痛程度和颈椎功能, 评价治疗效果。结果 干预后, 两组疼痛视觉模拟评分(VAS)和颈椎功能障碍指数(NDI)评分均较干预前下降, 且观察组VAS和NDI量表评分低于对照组, 差异有统计学意义(P＜0. 01)。观察组总有效率高于对照组(P＜0. 05)。结论 牛角罐法能改善颈椎病患者颈椎功能, 减轻患者的疼痛, 具有良好的临床应用价值。)